Helēnas Ledus - Starcas herbāriji - Jamonte, Daiga (My University, 2022)
Raksts par Helēnas Ledus-Starcas (1915 – 2005) herbārijiem Herbarium Latvicum (RIG II), kas glabājas Latvjas Universitātes Muzeja Botānikas un mikoloģijas kolekcijās.

Article about the herbariums of Helena Ledus-Starca (1915 – 2005) Herbarium Latvicum (RIG II) kept in the collections of Botany and Mycology of the Museum of the University of Latvia
Helenas Ledus - Starcs herbariums
Keywords: Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology::Plant physiology; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Herbarium Latvicum; Helēna Ledus; Helēna Starca; Latvijas flora; botānika; botany